Immune-related adverse events of anti-PD-1 immune checkpoint inhibitors: a single center experience - Sebestyén, Enikő; Major, Nóra; Bodoki, Levente; Makai, Attila; Balogh, Ingrid; Tóth, Gábor; Orosz, Zsuzsanna; Árkosy, Péter; Vaskó, Attila; Hodosi, Katalin; Szekanecz, Zoltán; Szekanecz, Éva (Frontiers in Oncology, 2023)
Objectives: Immune checkpoint inhibitors (ICIs) stimulate antitumor immune responses and, in parallel, they might trigger autoimmune and other immunopathological mechanisms eventually leading to immune-related adverse events (irAE). In our study, we assessed patients with malignancies who underwent anti-PD-1 treatment at the University of Debrecen, Clinical Center. Patients and methods: Between June 2017 and May 2021, 207 patients started ICI treatment at our university. A total of 157 patients received nivolumab and 50 were treated with pembrolizumab. We looked for factors associated with the development of irAEs. In addition to correlation studies, we performed binary logistic regression analysis to determine, which factors were associated with irAEs. We also performed Forward Likelihood Ratio (LR) analysis to determine independent prognostic factors. Results: At the time of data analysis, the mean duration of treatment was 2.03 ± 0.69 years. ROC analysis determined that 9 or more treatment cycles were associated with a significantly higher risk of irAEs. A total of 125 patients received ≥9 treatment cycles. Three times more patients were treated with nivolumab than pembrolizumab. Of the 207 patients, 66 (32%) developed irAEs. Among the 66 patients who developed irAEs, 36 patients (55%) developed one, 23 (35%) developed two, while 7 (10%) developed three irAEs in the same patient. The most common irAEs were thyroid (33 cases), dermatological (25 cases), pneumonia (14 cases) and gastrointestinal complications (13 cases). Patients who developed irAEs received significantly more treatment cycles (21.8±18.7 versus 15.8±17.4; p=0.002) and were younger at the start of treatment (60.7±10.8 versus 63.4±10.1 years; p=0.042) compared to patients without irAEs. Pembrolizumab-treated patients developed more but less severe irAEs compared to those receiving nivolumab. Conclusion: ICI treatment is very effective, however, irAEs may develop. These irAEs might be related to the number of treatment cycles and the type of treated malignancy.